ERMAP: ECC-based robust mutual authentication protocol for smart grid communication with AVISPA simulations. (5th October 2022) - Rajaram, Sangeetha; Vollala, Satyanarayana; Ramasubramanian, N.
Veracious new architectures and authentication protocols have been proposed by researchers to provide better security solutions for smart grid application. This paper analyses and discusses the limitations of the pairing-based authentication protocol proposed by Khalid Mahmood and others. It also proposes an ECC-based robust mutual authentication protocol for smart grid communication with AVISPA simulations called ERMAP that overcomes the limitations of Khalid Mahmood and others authentication protocol. ERMAP does authentication between end-user ( Ui ) and the smart meter ( SMe ) along with the authentication between service provider ( SPr ) and the SMe to add the security strength, which is not done by most of the authentication techniques used in smart grid systems. A formal model of ERMAP protocol has been implemented in the AVISPA tool using high-level protocol specification language (HLPSL). Also the results show better security strength. ( SMe ) theft issue, DOS attack, and other related attacks are addressed by ERMAP that are essential now a day, but not supported by many of the authentication techniques used in smart grid systems. ERMAP protocol does not need an extra supporting system to ensure ( SMe ) security. Computation cost and communication overhead of ERMAP is considerably less when compared with most of the other related authentication techniques.